To solve the statement first, we perform the operations step by step:
- Start with 10.
- Subtract 2: \(10 - 2 = 8\).
- Then, add 4: \(8 + 4 = 12\).
Now we can check which expression matches this sequence of operations:
A. \(10 - 2 + 4\)
- This simplifies to \(8 + 4 = 12\). (Matches)
B. \(10 - 4 + 2\)
- This simplifies to \(6 + 2 = 8\). (Does not match)
C. \(10 - 2 - 4\)
- This simplifies to \(8 - 4 = 4\). (Does not match)
D. \(2 - 10 + 4\)
- This simplifies to \(-8 + 4 = -4\). (Does not match)
The expression that matches the statement is A. \(10 - 2 + 4\).